Multimodal Neuroprotective Perspectives of Black Tea in Early Onset of Alzheimer- A New Paradigm - Bhandari, Koushik (International Journal of Pharmaceutical & Biological Archive, 2017)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder with far reaching consequences. Therapeutic options assuring total recovery is not available till yet. Adjuvant therapy has attracted the research limelight and now equal importance is being given to dietary and lifestyle interventions parallel with western classical medicine. Therapeutic entities are being developed with multimodal and translational perspectives. Adjuvant therapy has gained prominence as it can treat most naturally without altering the normal lifestyle. This review aims to highlight the putative neuroprotective, neurostimulatory and antioxidant effects of potent black tea compounds like theaflavins, catechins, L-theanine, caffeine where a multimodal therapeutic remedy can be achieved with L-theanine that can successfully cross the blood brain barrier coupled with free radical scavenging capacity of theaflavins and the synergistic improvement in cognitive performance with L-theanine-caffeine combination. Development of black tea formulations to combat bioavailability issues also fulfills the translational purposes.